2011
DOI: 10.1007/s10725-011-9571-4
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant enzymatic protection during tobacco leaf ageing is affected by cytokinin depletion

Abstract: Plant ageing and senescence are associated with increased levels of reactive oxygen species. Level of cytokinins, the apparent inhibitors of plant senescence, is controlled by their irreversible degradation catalysed by cytokinin oxidase/dehydrogenase (CKX). We investigated the CKX activity, cytokinin concentration, and activities of antioxidative enzymes in tobacco (Nicotiana tabacum L. cv. Samsun NN) overexpressing the Arabidopsis gene for AtCKX2, targeted for extracellular secretion pathway. The control and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 59 publications
0
9
0
1
Order By: Relevance
“…In this study, one cytokinin dehydrogenase was significantly up-regulated in the root tissue of Hua 11 by NaCl-treatment. Due to the fact that the concentrations of endogenous cytokine can be reduced by the cytokinin dehydrogenase, the antioxidative enzyme activity increases as cytokine decreases [72]. Therefore, the barley salt stress tolerance may be improved by the enhancement of antioxidant enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, one cytokinin dehydrogenase was significantly up-regulated in the root tissue of Hua 11 by NaCl-treatment. Due to the fact that the concentrations of endogenous cytokine can be reduced by the cytokinin dehydrogenase, the antioxidative enzyme activity increases as cytokine decreases [72]. Therefore, the barley salt stress tolerance may be improved by the enhancement of antioxidant enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the excess of CKs in plant often affects cellular processes, that are not otherwise under the regulation of CKs. Interestingly, using a reverse approach, it has been shown that reduced CK levels affect activities of antioxidant enzymes during the life span of tobacco [149]. For example, transgenic tobacco overexpressing Arabidopsis AtCKX2 under the control of a constitutive 35S promoter revealed enhanced activities of SOD, glutathione reductase (GR) and ascorbate peroxidase (APX) [149].…”
Section: Cks Enhance Antioxidant Defense Systemsmentioning
confidence: 99%
“…Plant hormones are known to be involved in antioxidant responses of many plants (Mýtinová et al, 2011). For example, an influence of exogenously applied cytokinin on catalase (CAT) and peroxidase (POD) activities has been observed in axillary multiplication of Pelargonium hortorum (Wojtania and Skrzypek, 2014), and adventitious shoot formation in Pinus strobus (Tang and Newton, 2005).…”
Section: Introductionmentioning
confidence: 99%